Pengaruh Terpaan Iklan di Instagram terhadap Minat Pengunjung Pariwisata di Dusun Semilir - Fitri Annisa, Rizka; Hariyanti, Puji (Program Studi Ilmu Komunikasi UII, 2024)
This research aims to prove whether there is an influence of advertising exposure and brand image on Instagram on the interest of tourism visitors to Dusun Semilir. The study was conducted by distributing questionnaires to 100 respondents who are followers of the Instagram account @dusunsemilir. The respondents answers were analyzed using multiple linear regression and normality tests. The results of this study show through statistical tests that there is a positive relationship. The positive regression coefficient values of X1 (advertising exposure on Instagram) and X2 (brand image), which are 0.335 and 0.396 respectively, indicate a direct relationship with Y (interest of Dusun Semilir visitors) according to the AISAS model. The R square value calculation of 0.543 shows the influence of variable X1 and X2 on Y by 54.3%.